(untitled) (Research, Society and Development, 2022)
Introduction: The improvement in the quality of life of patients with head and neck cancer has been the subject of studies, however hearing loss is one of the side effects of cancer treatment that significantly affect the quality of life of its patient, especially when radiotherapy is performed combined with cisplatin. Objective: To analyze the audiological findings of participants with head and neck cancer who underwent radiotherapy alone and concomitantly with cisplatin. Methodology: Participants with anatomopathological diagnosis of cancer of the head and neck who were at the end of cancer treatment, with normal hearing threshold prior to anticancer treatment, were included. Two groups were listed: Radiotherapy (RT) and chemotherapy concomitant with radiotherapy (QTRT). The QTRT participants used cisplatin, a drug from the Platinum Group at a dose between 200 and 300mg. Among the procedures performed are: anamnesis, otoscopy and conventional pure tone audiometry. Results: 22 subjects participated, with a mean age of 48.48 years, mostly men (68.2%). It was found that 59.1% had sensorineural hearing loss. The RT group consisted of 10 participants, 25% reported tinnitus and 38.5% were diagnosed with hearing loss. The QTRT with 12 participants reported tinnitus (25%) and 61.5% developed hearing loss. There was no statistically significant difference between groups for hearing thresholds in the frequencies under test. Conclusion: Patients undergoing antineoplastic treatment had significant side effects related to the hearing organ, and for treatment with concomitant chemotherapy and radiotherapy, the presence of hearing loss was significant.